Analysis of the particle size distribution of runoff sediment transported from water hyacinth fiber mat - Chow M.F.; Hashrim H. (American Institute of Physics Inc., 2023)
The uses of natural fibre mat for soil erosion control is increasingly popular due to the present-day need of alternate sustainable materials. This study is aimed to analyze the particle size distribution of sediment runoff transported from water hyacinth fiber mat under artificial rainfall. The natural fiber mat used in the study was made from the stem of water hyacinth with opening size of 30mm x 30mm. The potential of water hyacinth fibre mat (WHFM) was evaluated in laboratory experiment for 30 slope under two types of rainfall intensities. The results showed that the mass of soil loss had reduced by averagely 83% when covered by WHFM compared to bare soil for both types of rainfall intensities. It can be seen that the sediments collected at 5, 10, 15 and 20 minutes during the simulated rainfall period were mainly soil particle that passed through the 0.30 mm sieve compared to sediments collected at 25 and 30 minutes that passing through 0.063mm sieve. WHFM was successfully proved that can be implemented as soil erosion control for hilly slope condition. 2019 Author(s).